2023
DOI: 10.3390/brainsci13101367
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Mitochondrial Dysfunction and Ferroptosis during Ischemia-Associated Central Nervous System Diseases

He-Yan Tian,
Bo-Yang Huang,
Hui-Fang Nie
et al.

Abstract: Cerebral ischemia, a leading cause of disability and mortality worldwide, triggers a cascade of molecular and cellular pathologies linked to several central nervous system (CNS) disorders. These disorders primarily encompass ischemic stroke, Alzheimer’s disease (AD), Parkinson’s disease (PD), epilepsy, and other CNS conditions. Despite substantial progress in understanding and treating the underlying pathological processes in various neurological diseases, there is still a notable absence of effective therapeu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 221 publications
0
3
0
Order By: Relevance
“…As Lin QS et al ( Lin et al, 2023 ) found that mitophagy could regulate iron ion levels through the ROS/HO-1/GPX4 axis, thereby alleviating cisplatin-induced ferroptosis in renal tubular epithelial cells. Another study indicated that the activity of mitophagy may be inhibited during the progression of ischemia-reperfusion injury in stroke, leading to excessive accumulation of iron ions in cells and subsequently inducing ferroptosis ( Tian et al, 2023 ). On the other hand, the dysregulation of iron metabolism and the occurrence of ferroptosis also control the autophagic flux of mitochondria in the ischemia-reperfusion injury model of stroke.…”
Section: The Role Of Mitophagy and Ferroptosis In Ischemic Reperfusio...mentioning
confidence: 99%
“…As Lin QS et al ( Lin et al, 2023 ) found that mitophagy could regulate iron ion levels through the ROS/HO-1/GPX4 axis, thereby alleviating cisplatin-induced ferroptosis in renal tubular epithelial cells. Another study indicated that the activity of mitophagy may be inhibited during the progression of ischemia-reperfusion injury in stroke, leading to excessive accumulation of iron ions in cells and subsequently inducing ferroptosis ( Tian et al, 2023 ). On the other hand, the dysregulation of iron metabolism and the occurrence of ferroptosis also control the autophagic flux of mitochondria in the ischemia-reperfusion injury model of stroke.…”
Section: The Role Of Mitophagy and Ferroptosis In Ischemic Reperfusio...mentioning
confidence: 99%
“…Mitochondrial dysfunction is a hallmark of ferroptosis and a necessary condition for the perpetuation of these reactions. In fact, increased Fe uptake promotes the generation of destructive hydroxyl radicals through the Fenton reaction thus perpetuating the chain reaction of lipid peroxidation, ultimately compromising membrane integrity [107], which leads to cell membrane disruption and cell death. Unlike apoptosis and necrosis, ferroptosis presents with its own cellular pathways.…”
Section: Iron (Fe) -Hdmentioning
confidence: 99%
“…Clinically, β-asarone is utilized to treat fever, delirium, phlegm, forgetfulness, dementia, deafness, tinnitus, heartburn, traumatic injury, and so on ( Hei et al, 2020 ; Saki et al, 2020 ). The cascade reactions induced by cerebral ischemia include the release of excitatory amino acids, apoptosis, intracellular calcium influx overload, inflammation, activation of calcium-dependent enzymes, nitric oxide free radical production, and so on ( She et al, 2023 ; Shin et al, 2020 ; Tian et al, 2023 ). β-asarone has been confirmed to have antioxidant and anti-inflammatory properties ( Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%